P161 Cough Intensity in Voluntary, Induced and Spontaneous Cough. (19th November 2012) - Lee, KK; Ward, K; Raywood, E; Moxham, J; Rafferty, GF; Birring, SS
Abstract : Introduction: Cough intensity is an important determinant of cough severity. We set out to investigate and compare the physiological characteristics and intensity of voluntary (VC), induced (IC) and spontaneous cough (SC) in subjects with chronic cough. Methods: 28 subjects with chronic cough (17 female, mean age 57 years) underwent measurement of oesophageal pressure (Poes), gastric pressure (Pga), normalised peak cough flow rate (PCFR) and peak abdominal electromyographic activity (EMG) were measured during (1) maximum VC (MVC), (2) capsaicin IC (2 doses: C5 and supra-C5; 1st effort in a bout) and (3) SC (mean of 1st efforts of all bouts), in a subset of patients (n=9). Cough efforts were categorised as bouts or single events and as true cough or expiratory reflex (ER: absence of preparatory inspiration). Results: MVC by definition was always a single effort and all efforts were true coughs; no subject initiated an ER during MVC manoeuvres. The majority of efforts in IC (C5) and SC occurred within coughing bouts. ERs were the most frequent type of efforts in both IC and SC, 61–67% of all efforts, but accounted for only one third of the initial efforts of bouts in both IC and SC; true cough was the most frequent 1st effort (Table 1 ). Cough intensity was greatest in MVC for all measures. Poes, Pga and EMGabd were similar for IC and SC, and were approximately 60–70% of MVC intensity. PCFR:PEFRp however, was significantly higher in SC compared to IC. The analysis was similar for supra-C5 stimulus with capsaicin. When restricted to the subgroup that underwent studies of all cough models (VC, IC and SC), the analysis was also similar. Conclusions: This is the first study of the physiology of cough in patients with chronic cough and spontaneous cough. MVC produces the most intense cough. The type of cough effort in IC and SC is similar but there were important differences in cough intensity (flow). The reason for this and its implications for the induced cough model are unclear and warrant further investigation.